Safety and Feasibility Study of A Hyperbaric Infrared Chamber Combining Hyperbaric Oxygen Therapy and Low Temperature Infrared Radiation - Dünnwald, Tobias; Pecher, Otto; Balan, Petru; Held, Julia; Zeiger, Thomas; Mur, Erich; Weiss, Günter; Blank, Cornelia; Schobersberger, Wolfgang (International Journal of Innovative Research in Medical Science, 2016)
Objective: The aim of both Hyperbaric Oxygen Therapy (HBO) and Low Temperature Infrared Technology (LIT) is to increase oxygen supply to tissues. Combining the two techniques could generate synergistic effects and balance potential detrimental effects of HBO (vasoconstriction) due to vasodilation induced by LIT. Since this combination of HBO and LIT (HBOIR) has never before been tested, the aim of this study was to evaluate the safety and feasibility of HBOIR. Methods: 12 healthy subjects completed 6 HBOIR sessions, each lasting 45 minutes with at least 30 minutes of pure oxygen administration at a constant overload pressure of 0.5 bar. Heat was applied via far infrared radiation. Physiological and ambient parameters in the chamber were recorded during the treatment. Mental state was assessed before and after each HBOIR session. Results: There were no adverse effects during or after the HBOIR sessions. We observed significant but not clinically-relevant increases in heart rate, core and skin surface temperature and oxygen saturation. Well-being was not impaired post treatment. Conclusion: HBOIR induces moderate whole body warming accompanied by low cardiovascular exertion. It was demonstrated that HBOIR under an overload pressure of 0.5 bar is safe and well tolerated by the group of healthy subjects.